2015
DOI: 10.1002/hbm.22774
|View full text |Cite
|
Sign up to set email alerts
|

From personal fear to mass panic: The neurological basis of crowd perception

Abstract: Recent studies have investigated the neural correlates of how we perceive emotions of individuals or a group of individuals using images of individual bodily expressions. However, it is still largely unknown how we perceive the emotion of a dynamic crowd. This fMRI study used realistic videos of a large group of people expressing fearful, happy or neutral emotions. Furthermore, the emotions were expressed by either unrelated individuals in the group or by an interacting group. It was hypothesized that the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 92 publications
(141 reference statements)
3
15
0
Order By: Relevance
“…We investigated the neural basis of witnessing a violent conflict using video clips of two individuals engaged in an aggressive interaction and by varying the focus of attention on the aggressor or the victim. The results reveal activation of a distributed set of regions that have also been associated with body and emotion perception, including the insula, PMC, EBA and FBA, consistent with previous studies on social interactions 2 7 27 28 29 30 31 32 .…”
Section: Discussionsupporting
confidence: 90%
“…We investigated the neural basis of witnessing a violent conflict using video clips of two individuals engaged in an aggressive interaction and by varying the focus of attention on the aggressor or the victim. The results reveal activation of a distributed set of regions that have also been associated with body and emotion perception, including the insula, PMC, EBA and FBA, consistent with previous studies on social interactions 2 7 27 28 29 30 31 32 .…”
Section: Discussionsupporting
confidence: 90%
“…Much behavioral evidence has been accumulated supporting this notion 6,7,1115,21,99103, but see 104 , although only a few recent fMRI studies have compared the neural representations of ensemble coding and individual processing 105107 . Cant and Xu 105,106 showed that PPA and LO were preferentially engaged in texture perception and object processing, respectively; and Huis in’t Veld and de Gelder 107 showed the greater anticipatory and action preparation activity in the areas including IPL, SPL, SFG, and premotor cortex for interactive body movement of a group of panicked people, compared to an unrelated movement of individuals. However, unlike prior work that used stimuli of simple texture patches and objects 105,106 or that removed the information about facial expression of people from their blurred video clips 107 , the current study examined the distinct neutral substrates underlying the processing of facial crowds with varying emotional expressions compared to the processing of individual emotion expressions, providing evidence for distinct mechanisms supporting them.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we focused on the direction of threat as communicated directly by the movement of the person toward or away from the observer. We reduced the visibility of facial expressions by blurring the faces of the actors (Borgomaneri, Vitale, & Avenanti, ; Borgomaneri, Vitale, Gazzola, & Avenanti, ; de Gelder et al, ; Hortensius & de Gelder, ; Huis In 't Veld & de Gelder, ; Kret et al, ; Sinke, Sorger, Goebel, & de Gelder, ). This was done to maintain the focus of the participant on the main aspect of stimulus and away from facial information extraction, identity recognition, and other nonrelevant processes, Of course, facial and bodily expressions are heavily intertwined.…”
Section: Discussionmentioning
confidence: 99%